A time-slot leasing-based QoS routing protocol over Bluetooth WPANs. (7th December 2006) - Chen, Yuh-Shyan; Lin, Tsung-Hung
In this paper, we investigate a new efficient QoS routing protocol based on the time-slot leasing mechanism over Bluetooth WPANs. The "transmission holding" problem is incurred because the master node is the communication bottleneck for each slave-master-slave communication in Bluetooth. To alleviate this problem, a time-slot leasing scheme is adaptively incorporated into our scheme to provide a completely new QoS routing protocol. This QoS routing protocol can additionally offer extra slave-to-slave QoS communication capability to effectively reduce the workload of the master node. Finally, simulation results demonstrate that this protocol can significantly improve the success ratio, delay time, throughput, and bandwidth utilisation.